Knowledge, attitude, and practice of senior dental students toward management of complications in exodontia - T Srinivasa Prasad; Govindarajan Sujatha; R Shanmuga Priya; M Ramasamy (Wolters Kluwer Medknow Publications, 2019)
Introduction: Dental graduates have a professional responsibility of being competent in managing the complications in exodontia, a very commonly performed procedure. Aim: The aim of this paper was to assess the knowledge, attitude, and practice of senior dental students toward the management of complications in exodontia. Materials and Methods: Four hundred dental students participated in the study voluntarily. Verbal consent was obtained after elaborating the purpose of the study. A short validated questionnaire consisting of 12 close-ended multiple choice questions was distributed to all the students. The questionnaires were collected back and results from fully filled questionnaires were tabulated in Microsoft Excel 2007. Results: Nearly 93.4% of the students perform extractions in their practice on a routine basis. Among those 32.5% of the students have encountered complications, out of which only 20% of the students are confident in managing them. The remaining 64.8% of students who have not encountered complications are not confident in managing the same. Conclusion: This study revealed the need for increase in cases which will in turn help the students to transfer their theoretical knowledge into professional skills.